PENERAPAN METODE TEACHING AT THE RIGHT LEVEL (TaRL) UNTUK MENINGKATKAN HASIL BELAJAR NILAI-NILAI PANCASILA - Sari, Ariyana; Mintohari; Kriswati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The research aims to provide a solution to the problem of low student learning outcomes in the material of Pancasila values. Classroom action research with two cycles was applied in this study. Each cycle consists of four stages namely planning, implementation, observation and reflection. The subjects of this study consisted of all 4th grade students of SDN Dukuh Kupang 1 Surabaya totaling 28 students. Data was collected using test and observation techniques. The results showed that student learning outcomes improved after applying the TaRL method to Pancasila learning. Proven by the completeness of student learning in the pre-cycle reached 25%, then increased by 18% in cycle I and cycle II experienced an increase of 57%. The average score of students in the pre-cycle was 62.21, then increased to 67.07 in cycle I, and in cycle II reached 79.79. The highest score in cycle I was 90, while cycle II was 92. The lowest score obtained by students in cycle I was 46, while cycle II was 70